The Effect of Fe Doping on the Magnetic and Magnetocaloric Properties of Mn5−xFexGe3. (6th March 2017) - Brock, Jeffrey; Bell-Pactat, Nathanael; Cai, Hong; Dennison, Timothy; Fox, Tucker; Free, Brandon; Mahyub, Rami; Nar, Austin; Saaranen, Michael; Schaeffer, Tiago; Khan, Mahmud
Abstract : The magnetic and magnetocaloric properties of a series of minutely doped M n 5 - x F e x G e 3 compounds that exhibit the D88 -type hexagonal crystal structure at room temperature have been investigated. For all Fe concentrations, the alloys are ferromagnetic and undergo a second-order ferromagnetic-to-paramagnetic transition near room temperature. Although the small Fe doping had little effect on the ferromagnetic transition temperatures of the system, changes in the saturation magnetization and magnetic anisotropy were observed. For x ≤ 0.15, all compounds exhibit nearly the same magnetic entropy change of 7 J/kg K, for a field change of 50 kOe. However, the magnitude of the refrigerant capacities increased with Fe doping, with values up to 108.5 J/kg and 312 J/kg being observed for field changes of 20 kOe and 50 kOe, respectively. As second-order phase transition materials, the M n 5 - x F e x G e 3 compounds are not subject to the various drawbacks associated with first-order phase transition materials yet exhibit favorable magnetocaloric effects.